2023
DOI: 10.1038/s41467-023-43475-w
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy-linked kinase CDKL5 phosphorylates voltage-gated calcium channel Cav2.3, altering inactivation kinetics and neuronal excitability

Marisol Sampedro-Castañeda,
Lucas L. Baltussen,
André T. Lopes
et al.

Abstract: Developmental and epileptic encephalopathies (DEEs) are a group of rare childhood disorders characterized by severe epilepsy and cognitive deficits. Numerous DEE genes have been discovered thanks to advances in genomic diagnosis, yet putative molecular links between these disorders are unknown. CDKL5 deficiency disorder (CDD, DEE2), one of the most common genetic epilepsies, is caused by loss-of-function mutations in the brain-enriched kinase CDKL5. To elucidate CDKL5 function, we looked for CDKL5 substrates u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…The current study used a phosphoproteomic screen in mice lacking the Cdkl5 gene to search for CDKL5 target proteins. 7 The authors identified the voltage-gated calcium channel, Cav2.3, as a phosphorylation target. Calcium channels are well-recognized modulators of cellular excitability and subcellular signaling 8 and numerous DEE are associated with mutations in the various calcium channel subtypes.…”
Section: Commentarymentioning
confidence: 99%
“…The current study used a phosphoproteomic screen in mice lacking the Cdkl5 gene to search for CDKL5 target proteins. 7 The authors identified the voltage-gated calcium channel, Cav2.3, as a phosphorylation target. Calcium channels are well-recognized modulators of cellular excitability and subcellular signaling 8 and numerous DEE are associated with mutations in the various calcium channel subtypes.…”
Section: Commentarymentioning
confidence: 99%